The Analysis of Soft Error in C-Elements - Norhuzaimin Julai; Ahmed M. A. Haidar; Abdul Rahman Kram (Institute of Advanced Engineering and Science, 2018)
Soft errors are a serious concern in state holders as it can cause temporarily malfunction of the circuit. C-element is one of the state holders that is used widely in the asynchronous circuit. In this paper, the investigation will focus on the vulnerability of two types of C-element towards soft errors. A framework has been proposed for the rate of error due to neutron spectrum energy that can cause failure in the state holder. Effective analysis has been conducted on two different C-elements at different nodes by using UMC90 nm technology and 180nm technology. Based on the vulnerability data, a method for assessing vulnerability on a different implementation of C-elements has been developed. From the obtained data, it can be concluded that SIL is more resistant towards soft errors.